2011
DOI: 10.1016/j.clcc.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of miR-215 in Colon Cancer

Abstract: The clinical utility of miR-215 as a potential biomarker in colon cancer was investigated. The levels of miR-215 were quantified by real-time qRT-PCR in 34 paired normal and tumor specimens. The expression levels of miR-215 were decreased in colon tumors, and were associated with patient survival. Thus, miR-215 is a potential prognostic biomarker in colon cancer. Background We have previously shown that miR-215 suppressed the expression of key targets such as thymidylate synthase (TS), dihydrofolate reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 44 publications
10
80
3
Order By: Relevance
“…Recent studies confirmed miR-215 downregulation in esophageal adenocarcinoma (Wijnhoven et al, 2010), colon cancer (Karaayvaz et al, 2011), and RCC (White et al, 2011). Decreased miR-215 levels in colorectal cancer were associated with increased tumor sizes and shorter disease-free survival after radical surgery (Chiang et al, 2012;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies confirmed miR-215 downregulation in esophageal adenocarcinoma (Wijnhoven et al, 2010), colon cancer (Karaayvaz et al, 2011), and RCC (White et al, 2011). Decreased miR-215 levels in colorectal cancer were associated with increased tumor sizes and shorter disease-free survival after radical surgery (Chiang et al, 2012;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…miR-215 is upregulated in cervical cancer , hepatocellular carcinoma , gastric cancer (Deng et al, 2014), and prostate cancer (Walter et al, 2013), and it acts as a potential oncogene in these tumors. On the contrary, the expression of miR-215 was found to be significantly decreased in esophageal adenocarcinoma (Wijnhoven et al, 2010), colon cancer (Karaayvaz et al, 2011), and renal cell carcinoma (RCC) (White et al, 2011), where it acts as a candidate tumor suppressor. However, the correlation between miR-215 dysregulation and clinicopathological characteristics of pancreatic cancer has not yet been evaluated, and the biological roles of miR-215 and its direct functional targets in pancreatic cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of miR-215 was demonstrated to be associated with the International Federation of Gynecology and Obstetrics stage, the histological grade, and the extents of vascular invasion and lymph node metastasis of cervical cancer; the 5-year survival rate was lower in patients with stage II cervical cancer who exhibited miR-215 overexpression (29). However, previous studies have also demonstrated that miR-215 may be downregulated in epithelial ovarian (30), pancreatic (31), non-small cell lung (32), breast (33) and colon (34) cancer. In the study on pancreatic cancer, a low expression level of miR-215 was significantly associated with a large tumor size, an advanced TNM stage, a high extent of lymph node metastasis and vessel invasion, and lower overall survival time; multivariate regression analysis demonstrated that miR-215 underexpression was an independent unfavorable prognostic factor for patients (31).…”
Section: Discussionmentioning
confidence: 87%
“…Although the cause of this discrepancy is unclear, we reason that miR-215 may act as a double-edged sword, modulating multiple targets and pathways. Karaayvaz et al reported that a high level of miR-215 suppresses tumor cell proliferation and increases cell cycle arrest [42]. The differential expression of miR-215 is reflected by the stage of transformation, dysplasia versus carcinoma.…”
Section: Discussionmentioning
confidence: 99%